Delineating classical schizophrenia: quantifying disorganization and the core deficit in classical schizophrenia and exploring their neural correlates - Rathnaiah, Mohanbabu (2024)
Despite the moderate efficacy of antipsychotic medication, many patients with psychotic illnesses continue to experience persisting symptoms and disability. The classical descriptions of schizophrenia by Kraepelin and Bleuler emphasize disorganization and impoverishment of mental activity together with impairment of cognition and role function. In this thesis, we examine the core classical features of disorganization, impoverishment, and cognitive dysfunction, along with impairment in role-function in psychotic illnesses. In addition, we examine the relationship between these classical features and reality distortion, the characteristic feature of florid episodes of psychosis. Methods of quantifying disorganization and impoverishment using systematic review of three common symptom scales is presented in Chapter1, along with methods to quantify formal thought disorder (FTD) using speech and language manifestations. Cognition as a core feature is presented with supporting evidence in Chapter 2 along with rationale for neural investigation tools that we employed. Chapter 3 presents confirmatory factor analysis (CFA) investigation of core features to identify a single latent variable of shared variance (classicality), termed putative core deficit, along with cluster analysis to try to seek the answer for dimensionality versus categorical nature of classicality. Chapter 4 presents maximum likelihood factor analysis (EFA) and cluster analysis in an independent sample with stable psychosis illness, but with advantage of availability of persistent measures of disorganization and impoverishment, in addition to current measures. Chapter 5 presents delineation of core deficit from a heterogenous multi-centre mix sample of recent onset and established schizophrenia. Chapter 6 presents neural correlates of classicality in the sample described in chapter 5. Relationship of core deficit with reality distortion and FTD is explored in all three independent samples, in addition to neural correlates. Our results demonstrate that a single latent variable of core deficit is derived from each of the three independent samples, and we further demonstrate in two samples that core deficit predicts reality distortion as well as positive correlation with FTD measure. We argue for core deficit to be a valid and replicable marker of classicality which can be targeted with focussed interventions to potentially ameliorate the burden of psychosis and to improve outcome. Through our cluster analysis, we demonstrate that classicality data fits into dimensional nature rather than discrete categories. Our results provide evidence for post-movement beta rebound (PMBR), an electrophysiology neural marker, to be diminished in proportion to the severity of core deficit. Limitations include small sample size, cross-sectional nature of data and potential confounding effect from variables such as medication exposure. We recommend for future large-scale research and clinical efforts towards potential development of a new scale utilising severity of core deficit, along with trials of focussed psychopharmacology and neuromodulation interventions to ameliorate the severity of core deficit.